Aramid nanofiber-reinforced thermoplastic composite structural battery and thermoplastic structural electrolyte membrane and preparation method
Patent Information
- Application Number
- CN202610863982.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-15
- Publication Date
- 2026-08-18
AI Technical Summary
[0006]针对现有结构电解质体系中力学性能与电化学性能难以协同提升、界面稳定性不足以及增强相与聚合物基体协同作用有限等问题,本发明旨在提供一种芳纶纳米纤维增强热塑性复合结构电池及热塑性结构电解质膜及制备方法,以提升结构电池的力学性能与电化学性能,满足高性能结构储能器件的应用需求
1.在材料体系层面,本发明通过在纤维素衍生物与聚合物共混形成的热塑性复合结构电解质中引入芳纶纳米纤维,实现了结构电池力学性能与电化学性能的协同提升。本发明利用芳纶纳米纤维高长径比、高模量及优异界面作用能力的特点,在聚合物复合基体内部构建稳定的增强网络结构。芳纶纳米纤维不仅能够提高复合结构电解质的强度、模量及界面稳定性,还能够优化聚合物内部微观结构,改善离子传输环境,从而在保证结构支撑能力的同时维持良好的离子传导性能。此外,芳纶纳米纤维的引入还能够增强复合结构电解质与碳纤维电极之间的界面结合能力,促进载荷在结构中的有效传递,提高结构电池整体的力学稳定性与循环稳定性。
Smart Images

Figure CN122599525A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of structural energy storage and electrochemical energy storage technology, specifically relating to an aramid nanofiber reinforced thermoplastic composite structure battery and a thermoplastic structure electrolyte membrane and its preparation method. Background Technology
[0002] In recent years, carbon fiber composite structure batteries, which combine mechanical load-bearing and electrical energy storage functions, have gradually become an important research direction in the field of structural energy storage, attracting widespread attention in lightweight applications such as aerospace, new energy vehicles, rail transportation, and intelligent electronic devices. Unlike traditional lithium-ion batteries that rely on independent packaging and external structural support, structural batteries integrate energy storage and structural functions by using carbon fiber composite materials as both electrode materials and load-bearing components. This effectively reduces system weight, improves space utilization efficiency, and promotes the development of energy systems towards lightweighting and high integration.
[0003] In structured battery systems, the structural electrolyte not only undertakes ion transport but also plays a role in stress transfer and interfacial bonding between electrodes. Therefore, its comprehensive performance directly affects the electrochemical and mechanical properties of the structured battery. Existing structural electrolytes mostly employ polymer-based composite systems, which, while providing some structural support, generally suffer from low ionic conductivity, insufficient interfacial stability, and difficulty in achieving a balance between mechanical and electrochemical performance: increasing the mobility of polymer chains to enhance ion migration often decreases the material's rigidity and structural stability; conversely, increasing the material's modulus and strength can restrict ion transport, thus limiting the overall performance of the structured battery.
[0004] To improve the overall performance of structural electrolytes, researchers have attempted to reinforce polymer systems by introducing inorganic fillers and nanoparticles. Nanofibers, with their high specific surface area, high aspect ratio, and excellent mechanical properties, are considered a key approach to enhancing the performance of structural electrolytes. However, existing reinforcing materials still have shortcomings in terms of dispersion in the polymer matrix, interfacial compatibility, and the regulation of ion transport behavior. While some reinforcing materials can improve the mechanical strength of the material, they can hinder the formation of ion migration channels, leading to a decline in electrochemical performance. Conversely, while some flexible polymer systems possess good ion conductivity, it is difficult to establish stable and effective interfacial reinforcement structures, failing to meet the high strength and high stability requirements of structural batteries.
[0005] Therefore, there is an urgent need to develop a composite electrolyte system that combines excellent ion transport capabilities, interfacial stability, and mechanical enhancement. By rationally introducing aramid nanofibers, the synergistic optimization between the polymer matrix, electrochemical performance, and structural support capabilities can be achieved, thereby improving the overall performance and engineering application potential of carbon fiber composite battery structures. Summary of the Invention
[0006] To address the problems of insufficient synergistic improvement of mechanical and electrochemical properties, inadequate interfacial stability, and limited synergistic effect between the reinforcing phase and the polymer matrix in existing structural electrolyte systems, this invention aims to provide an aramid nanofiber-reinforced thermoplastic composite battery, a thermoplastic structural electrolyte membrane, and a preparation method thereof, in order to improve the mechanical and electrochemical properties of the structural battery and meet the application requirements of high-performance structural energy storage devices.
[0007] The primary objective of this invention is to provide a thermoplastic structural electrolyte membrane. This thermoplastic structural electrolyte membrane is constructed by introducing an appropriate amount of aramid nanofibers into a polymer composite matrix formed by blending cellulose derivatives and polymers. Through the synergistic effect between the aramid nanofibers and the polymer, a composite structural electrolyte with both ion conduction and structural support capabilities is constructed. The aramid nanofibers can improve the microstructure and interfacial bonding state of the composite structural electrolyte, enhance interlayer synergy, and promote the effective transfer of load within the structure, thereby improving the mechanical and electrochemical performance of the structural battery.
[0008] Another objective of this invention is to provide a method for preparing a thermoplastic electrolyte membrane incorporating aramid nanofibers. This method involves uniformly dispersing a polymer composite matrix, lithium salt, and aramid nanofibers through a solution blending process, and constructing a stable composite structure through a controllable film-forming process. This improves the mechanical properties, interfacial stability, and structural integrity of the composite electrolyte while ensuring ion transport performance.
[0009] Another objective of this invention is to provide a thermoplastic composite battery reinforced with aramid nanofibers based on a thermoplastic electrolyte membrane and its assembly method. This method integrates carbon fiber electrodes with a thermoplastic composite electrolyte through a hot-pressing composite process, achieving a tight interfacial bond between the electrodes and the electrolyte under certain temperature and pressure conditions, thereby obtaining a structural battery that combines energy storage and load-bearing capabilities.
[0010] Another object of the present invention is to provide the application of the aramid nanofiber-reinforced thermoplastic composite structure battery in lightweight structural energy storage systems. The structural battery constructed based on the thermoplastic electrolyte membrane not only possesses good cycle stability but also high structural load-bearing capacity and mechanical properties, and can be applied in aerospace, electric vehicles, and other lightweight integrated energy storage fields.
[0011] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing a thermoplastic electrolyte membrane includes the following steps: Preparation of polymer composite precursor solution: Lithium salt and polyether electrolyte are dissolved in... N,NIn dimethylformamide, the mass ratio of the three components is 1:9:90; the cellulose derivative is dissolved in... N,N In dimethylformamide, the mass ratio of the two is 10:90; Solution mixing: Mix the two solutions above in a mass ratio of 7:3 and stir until homogeneous and transparent. This mixture is denoted as solution A. Preparation of aramid nanofiber dispersion: Poly(p-phenylene terephthalamide) and potassium hydroxide were mixed at a mass ratio of 2:3 and then stirred thoroughly in dimethyl sulfoxide to ensure uniform dispersion. Deionized water was then added at a volume ratio of 1:25 to dimethyl sulfoxide, and the mixture was magnetically stirred until a homogeneous and stable dark red aramid nanofiber / dimethyl sulfoxide dispersion was obtained, denoted as solution B. The solid content of aramid nanofibers in the resulting dispersion was 0.5 wt.%. Preparation of composite electrolyte: Add an appropriate amount of solution A to solution B, control the aramid nanofibers to account for 1 wt.% of the total mass of solution A, and continue stirring to make the aramid nanofibers uniformly dispersed in the system, thus obtaining an aramid nanofiber reinforced thermoplastic composite electrolyte solution. Defoaming and film formation: After defoaming the mixed solution in a defoaming machine, it is poured into a polytetrafluoroethylene mold and left to stand in an inert atmosphere at 25±2℃ for 12 hours to allow the solvent to partially evaporate and form a primary film. Vacuum drying: The nascent membrane was vacuum dried at 70 °C and a pressure below 0.1 kPa for 24 hours to obtain a thermoplastic electrolyte membrane with a thickness of 300±50 μm; Storage: Store the dried thermoplastic structured electrolyte membrane in an inert atmosphere with both water and oxygen content below 0.1 ppm.
[0012] An aramid nanofiber-reinforced thermoplastic composite battery is obtained based on the thermoplastic electrolyte membrane of the present invention.
[0013] An assembly method for an aramid nanofiber-reinforced thermoplastic composite battery includes the following steps: Step 1: Prepare a thermoplastic electrolyte membrane; Step 2, Structural Battery Module Layup: The thermoplastic structural electrolyte membrane, carbon fiber structural negative electrode, thermoplastic structural electrolyte membrane, glass fiber separator, thermoplastic structural electrolyte membrane, carbon fiber structural positive electrode, and thermoplastic structural electrolyte membrane are laid up in sequence. Step 3: Hot pressing: The battery layers are placed in a hot press and heated under a certain pressure to complete the thermoplastic forming of the structural battery. Step 4, Post-processing: Store the shaped battery in an inert atmosphere.
[0014] An aramid nanofiber reinforced thermoplastic composite battery is proposed for applications in aerospace, electric vehicles, and lightweight integrated energy storage.
[0015] Compared with the prior art, the technical solution of this invention has the following outstanding advantages: 1. At the materials system level, this invention achieves a synergistic improvement in the mechanical and electrochemical performance of the structural battery by introducing aramid nanofibers into a thermoplastic composite electrolyte formed by blending cellulose derivatives with polymers. This invention utilizes the high aspect ratio, high modulus, and excellent interfacial interaction capabilities of aramid nanofibers to construct a stable reinforcing network structure within the polymer composite matrix. Aramid nanofibers not only improve the strength, modulus, and interfacial stability of the composite electrolyte but also optimize the internal microstructure of the polymer and improve the ion transport environment, thereby maintaining good ion conductivity while ensuring structural support. Furthermore, the introduction of aramid nanofibers enhances the interfacial bonding between the composite electrolyte and the carbon fiber electrode, promoting effective load transfer within the structure and improving the overall mechanical and cycle stability of the structural battery.
[0016] 2. In terms of structural battery construction and application, this invention achieves highly efficient integrated construction between a thermoplastic composite electrolyte and a carbon fiber electrode. Through a hot-pressing composite process, the thermoplastic composite electrolyte can form a tight interface bond with the carbon fiber electrode under certain temperature and pressure conditions, constructing an integrated structural battery that combines energy storage and load-bearing capacity. Compared to the traditional approach of separating battery cells from external structures, the structural battery constructed by this invention effectively reduces the mass of additional structures, improves space utilization, and enhances overall structural integration. Simultaneously, the thermoplastic composite electrolyte exhibits excellent processing adaptability and structural designability, meeting the integration requirements of complex-shaped structural components, allowing energy storage functionality to be directly integrated into load-bearing components. Based on these characteristics, the structural battery provided by this invention has broad application prospects in aerospace, electric vehicles, and other lightweight energy structure systems, providing a new technical solution for the development of structural energy storage devices towards high performance, integration, and engineering. Attached Figure Description
[0017] Figure 1 Optical photographs of some of the raw materials used in the preparation of thermoplastic electrolyte membranes. Figure 1 Image a is an optical photograph of the poly(p-phenylene terephthalamide) fiber provided by this invention. Figure 1 Image b is an optical photograph of the aramid nanofiber dispersion. Figure 1 Image c in the image is a transmission electron microscope (TEM) image of aramid nanofibers.
[0018] Figure 2Optical photographs of thermoplastic composite electrolytes with different aramid nanofiber contents.
[0019] Figure 3 This is a schematic diagram showing the tensile properties of a thermoplastic electrolyte membrane and its corresponding composite battery. Figure 3 Figure 'a' is a schematic diagram showing the tensile properties of this thermoplastic electrolyte membrane. Figure 3 In the diagram, b represents the tensile properties of the corresponding composite structure battery.
[0020] Figure 4 This provides the ionic conductivity of thermoplastic electrolyte membranes and the long-cycle data for corresponding composite battery structures. Detailed Implementation
[0021] To make the technical problems solved, technical solutions, and beneficial effects of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention. Any supplements, equivalent substitutions, or modifications made within the technical scope of this invention should be included within the protection scope of this invention.
[0022] A method for preparing a thermoplastic electrolyte membrane includes the following steps: Preparation of polymer composite precursor solution: Lithium salt and polyether electrolyte are dissolved in... N,N In dimethylformamide, the mass ratio of the three components is 1:9:90; the cellulose derivative is dissolved in... N,N In dimethylformamide, the mass ratio of the two is 10:90; Solution mixing: Mix the two solutions above in a mass ratio of 7:3 and stir until homogeneous and transparent. This mixture is denoted as solution A. Preparation of aramid nanofiber dispersion: Poly(p-phenylene terephthalamide) and potassium hydroxide were mixed at a mass ratio of 2:3 and then stirred thoroughly in dimethyl sulfoxide to ensure uniform dispersion. Deionized water was then added at a volume ratio of 1:25 to dimethyl sulfoxide, and the mixture was magnetically stirred until a homogeneous and stable dark red aramid nanofiber / dimethyl sulfoxide dispersion was obtained, denoted as solution B. The solid content of aramid nanofibers in the resulting dispersion was 0.5 wt.%. Preparation of composite electrolyte: Add an appropriate amount of solution A to solution B, control the aramid nanofibers to account for 1 wt.% of the total mass of solution A, and continue stirring to make the aramid nanofibers uniformly dispersed in the system, thus obtaining an aramid nanofiber reinforced thermoplastic composite electrolyte solution. Defoaming and film formation: After defoaming the mixed solution in a defoaming machine, it is poured into a polytetrafluoroethylene mold and left to stand in an inert atmosphere at 25±2℃ for 12 hours to allow the solvent to partially evaporate and form a primary film. Vacuum drying: The nascent membrane was vacuum dried at 70 °C and a pressure below 0.1 kPa for 24 hours to obtain a thermoplastic electrolyte membrane with a thickness of 300±50 μm; Storage: Store the dried thermoplastic structured electrolyte membrane in an inert atmosphere with both water and oxygen content below 0.1 ppm.
[0023] Preferably, the polyether electrolyte of the present invention is polyethylene oxide (PEO); the cellulose derivative is cellulose acetate (CA); the aramid nanofiber is aramid nanofiber ANF after dispersion treatment; and the lithium salt is lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).
[0024] A method for preparing an aramid nanofiber reinforced thermoplastic composite battery includes the following steps: Step 1: Prepare a thermoplastic electrolyte membrane; Step 2, Structural Battery Module Layup: The thermoplastic structural electrolyte membrane, carbon fiber structural negative electrode, thermoplastic structural electrolyte membrane, glass fiber separator, thermoplastic structural electrolyte membrane, carbon fiber structural positive electrode, and thermoplastic structural electrolyte membrane are laid up in sequence. Step 3: Hot pressing: The battery layers are placed in a hot press and heated under a certain pressure to complete the thermoplastic forming of the structural battery. Step 4, Post-processing: Store the shaped battery in an inert atmosphere.
[0025] Preferably, in step two of the present invention, the size of the carbon fiber structure negative electrode is 5 cm × 6 cm, and the size of the carbon fiber structure positive electrode is 4.6 cm × 5.6 cm.
[0026] Preferably, in step three of the present invention, the hot pressing process is as follows: programmed temperature increase pressing is performed under a pressure of 5 MPa, initially at a rate of 10 °C / min from 30 °C. The temperature is increased from 80 °C to 80 °C, then increased to 120 °C at a rate of 5 °C / min, and held at 120 °C for 20 minutes.
[0027] Preferably, the inert atmosphere in step four of the present invention is an argon atmosphere.
[0028] The aramid nanofiber reinforced thermoplastic composite battery of the present invention has applications in aerospace, electric vehicles and lightweight integrated energy storage.
[0029] The following examples disclose a method for preparing an aramid nanofiber reinforced thermoplastic composite electrolyte and a carbon fiber composite battery.
[0030] Example 1: Preparation of aramid nanofiber reinforced thermoplastic composite thermoplastic structure electrolyte membrane:
[0031] This embodiment aims to illustrate the specific preparation method of the composite polymer electrolyte membrane of the present invention, and to verify the influence of different proportions of aramid nanofibers on its performance.
[0032] A method for preparing a thermoplastic electrolyte membrane includes the following steps: (1) Raw materials and equipment: LiTFSI (battery grade), PEO (M w = 600,000), poly(p-phenylene terephthalamide) (PPTA, 6mm), cellulose acetate (CA, acetyl content 39.8%), potassium hydroxide (KOH, 99%), dimethyl sulfoxide (DMSO), DMF (anhydrous grade). Magnetic stirrer, PTFE mold, glove box (water and oxygen content <0.1 ppm), vacuum drying oven.
[0033] (2) Preparation process: First, a PEO-based mixed precursor solution was prepared: LiTFSI and PEO were dissolved in DMF at a mass ratio of 1:9:90; CA was dissolved in DMF at a mass ratio of 10:90; the two were mixed at a mass ratio of 7:3 and stirred until homogeneous and transparent, and this solution was designated as solution A; then, an ANF dispersion was prepared: PPTA and KOH were mixed at a mass ratio of 2:3, DMSO was added and stirred thoroughly, and then deionized water was added at a volume ratio of 1:25 to DMSO to obtain a homogeneous and stable deep red ANF / DMSO dispersion, designated as solution B. Figure 1 (a) shows an optical photograph of PPTA fibers and the ANF dispersion obtained after deprotonation. The obtained ANF dispersion exhibits a uniform and stable state and displays the Tyndall effect. Figure 1 (b) indicates that the PPTA fibers have been successfully dispersed in nanoscale. Figure 1 c is a TEM image of ANF, which shows a distinct nanofiber morphology. The fibers are slender and flexible with a high aspect ratio, forming a relatively loose network structure.
[0034] (3) Blending and Film Formation: An appropriate amount of A was added to the precursor solution B (denoted as ANF / PC), controlling the ANF content in solution A to be 1 wt.% of the mass of solution B, to obtain an ANF-reinforced thermoplastic composite electrolyte solution. The mixed solution was defoamed using a defoamer and then poured into a polytetrafluoroethylene mold. It was then allowed to stand for 12 hours in an inert atmosphere at 25±2 °C to allow partial solvent evaporation and form a nascent film. Subsequently, the nascent film was vacuum dried for 24 hours at 70 °C and a pressure below 0.1 kPa to obtain a thermoplastic electrolyte membrane with a thickness of 300±50 µm. Optical photographs of the electrolyte membrane are shown below. Figure 2As shown in a, Figure 2 Images b and 2c show SEM images of the front and cross-section of the electrolyte membrane. After introducing a small amount of ANF, the surface morphology of the 0.5ANF / PC, 1ANF / PC, and 2ANF / PC samples remained relatively intact, with good membrane continuity and no obvious large-scale pores or through cracks. Their cross-sectional structures also exhibited high density. This indicates that ANF can be well dispersed in the PEO / CA matrix and does not significantly disrupt the film formation process of the composite electrolyte membrane.
[0035] Example 2: Assembly and electrochemical performance testing of carbon fiber composite material structure battery
[0036] This embodiment aims to illustrate the process of assembling a battery using the electrolyte membrane (1ANF / PC) in Example 1 and the electrochemical performance of the resulting battery.
[0037] (1) Electrode materials: lithium iron phosphate (LiFePO4, battery grade), lithium titanate (LTO, battery grade), conductive carbon black (battery grade), polyvinylidene fluoride (PVDF, battery grade), N-methylpyrrolidone (NMP, battery grade), carbon fiber fabric (T800-12K), glass fiber diaphragm (GF / A).
[0038] (2) Battery assembly preparation: Electrodes: Carbon fiber fabric is used as the electrode substrate. A slurry is prepared according to the ratio of active material: conductive carbon black: PVDF binder = 7:2:1 (LiFePO4 for the positive electrode and LTO for the negative electrode). The solvent is N-methylpyrrolidone (NMP). The active material is coated on both sides of the carbon fiber using a doctor blade. The separator is a glass fiber separator. The electrolyte membrane is the 1ANF / CA membrane prepared in Example 1.
[0039] (2) Hot-press integrated assembly: Layup is performed in the following order: 1 ANF / PC membrane, carbon fiber anode, 1 ANF / PC membrane, glass fiber separator, 1 ANF / PC membrane, carbon fiber cathode, 1 ANF / PC membrane. Then it is placed between the plates of a hot press, a constant pressure of 5 MPa is applied, and the temperature is increased according to the program: at 10... o C / min from 30 o The temperature is raised to 80 °C, then increased to 120 °C at a rate of 5 °C / min, and held at 120 °C for 20 min. Afterward, it is allowed to cool naturally to room temperature, and then demolded to obtain an integrated carbon fiber composite material structure battery.
[0040] (3) Electrochemical and mechanical performance testing Mechanical properties: such as Figure 3 As shown in Figure a, the tensile strength of the composite electrolyte is 13.23 MPa. A standard tensile specimen was cut from the molded structural battery and its tensile strength was tested. Figure 3b) is 393.58 MPa, which proves that it has excellent mechanical load-bearing performance.
[0041] Coin cell testing: The composite electrode / electrolyte unit from the above-described battery structure was cut into discs and assembled into CR2032 coin cells for testing. Ionic conductivity at different temperatures was measured as follows: Figure 4 As shown in Figure a, the battery structure can stably cycle 100 times under charge-discharge conditions of 60 °C and 0.1C, with a capacity retention rate of 73.7%. Figure 4 b).
[0042] Comparative Example Comparative Example 1: Polymer composite electrolytes and structural batteries with different aramid nanofiber solid contents This comparative example shows composite electrolytes and structural batteries made of aramid nanofibers with different solid contents, in order to compare their performance limitations.
[0043] (1) Electrolyte preparation: The preparation method is consistent with that in Example 1, except that the solid content of ANF in the PEO composite polymer precursor solution is different.
[0044] (2) Battery assembly and testing: The preparation method is consistent with that in Example 2, except that the solid content of ANF in the PEO precursor solution is different.
[0045] 1. Electrochemical Performance Comparison: The ionic conductivity initially increases and then decreases with increasing ANF solid content. Compared to the ionic conductivity of the 1ANF / PC membrane of this invention, the ionic conductivity of 0ANF / PC, 0.5ANF / PC, and 2ANF / PC membranes decreases by 22%, 11%, and 42%, respectively. The corresponding capacity retention rates of the resulting battery structures after 100 cycles at 0.1C decrease by 45%, 20%, and 64%, respectively.
[0046] 2. Comparison of Mechanical Properties: With the increase of ANF solid content, the tensile strength, tensile modulus, and flexural strength of the corresponding battery structures all showed significant improvement. Compared with the 1ANF / PC structure battery of this invention, the tensile strength of the 0ANF / PC and 0.5ANF / PC structure batteries decreased by 27.8% and 17.1%, respectively; the tensile modulus decreased by 40.7%, 14.6%, and 8.8%, respectively; and the flexural strength decreased by 28.9% and 14.9%, respectively. In contrast, the 2ANF / PC structure battery, compared with the 1ANF / PC structure battery, showed an increase in tensile strength, tensile modulus, and flexural strength of approximately 10.4%, 9.7%, and 11.4%, respectively.
[0047] Conclusion: Through comparison of the embodiments and comparative examples of the present invention, it is fully demonstrated that the aramid nanofiber-reinforced thermoplastic composite electrolyte and its carbon fiber composite structure battery provided by the present invention achieve further improvement in the electrochemical performance of the structure battery while maintaining excellent mechanical properties. The introduction of an appropriate amount of aramid nanofiber reinforcing phase can effectively improve the electrochemical performance of the structure battery; at the same time, with the increase of aramid nanofiber content, the mechanical properties of the structure battery are significantly enhanced, achieving an effective balance between energy storage performance and mechanical performance in the structure battery.
Claims
1. A method for preparing a thermoplastic electrolyte membrane, characterized in that... Includes the following steps: Preparation of polymer composite precursor solution: Lithium salt and polyether electrolyte are dissolved in... N,N In dimethylformamide, the mass ratio of the three components is 1:9:90; the cellulose derivative is dissolved in... N,N In dimethylformamide, the mass ratio of the two is 10:90; Solution mixing: Mix the two solutions above at a mass ratio of 7:3 and stir until homogeneous and transparent. This mixture is denoted as solution A. Preparation of aramid nanofiber dispersion: Poly(p-phenylene terephthalamide) and potassium hydroxide were mixed at a mass ratio of 2:3 and then stirred thoroughly in dimethyl sulfoxide to ensure uniform dispersion. Deionized water was then added at a volume ratio of 1:25 to dimethyl sulfoxide, and the mixture was magnetically stirred until a homogeneous and stable dark red aramid nanofiber / dimethyl sulfoxide dispersion was obtained, denoted as solution B. The solid content of aramid nanofibers in the resulting dispersion was 0.5 wt.%. Preparation of composite electrolyte: Add an appropriate amount of solution A to solution B, control the aramid nanofibers to account for 1 wt.% of the total mass of solution A, and continue stirring to make the aramid nanofibers uniformly dispersed in the system, thus obtaining an aramid nanofiber reinforced thermoplastic composite electrolyte solution. Defoaming and film formation: After defoaming the mixed solution in a defoaming machine, it is poured into a polytetrafluoroethylene mold and left to stand in an inert atmosphere at 25±2 ℃ for 12 hours to allow the solvent to partially evaporate and form a primary film. Vacuum drying: The nascent membrane was vacuum dried at 70 °C and a pressure below 0.1 kPa for 24 hours to obtain a thermoplastic electrolyte membrane with a thickness of 300±50 μm. Storage: Store the dried thermoplastic structured electrolyte membrane in an inert atmosphere with both water and oxygen content below 0.1 ppm.
2. The preparation method according to claim 1, characterized in that... The polyether electrolyte is polyethylene oxide (PEO); the cellulose derivative is cellulose acetate (CA); the aramid nanofiber is aramid nanofiber ANF after dispersion treatment; and the lithium salt is lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).
3. A thermoplastic electrolyte membrane obtained by the preparation method according to claim 1.
4. An aramid nanofiber reinforced thermoplastic composite battery based on the thermoplastic electrolyte membrane of claim 3.
5. A method for assembling the aramid nanofiber reinforced thermoplastic composite battery of claim 4, characterized in that, Includes the following steps: Step 1: Prepare a thermoplastic electrolyte membrane; Step 2, Structural Battery Module Layup: The thermoplastic structural electrolyte membrane, carbon fiber structural negative electrode, thermoplastic structural electrolyte membrane, glass fiber separator, thermoplastic structural electrolyte membrane, carbon fiber structural positive electrode, and thermoplastic structural electrolyte membrane are laid up in sequence. Step 3: Hot pressing: The battery layers are placed in a hot press and heated under a certain pressure to complete the thermoplastic forming of the structural battery. Step 4, Post-processing: Store the shaped battery in an inert atmosphere.
6. The assembly method according to claim 5, characterized in that, In step two, the dimensions of the carbon fiber negative electrode are 5 cm × 6 cm, and the dimensions of the carbon fiber positive electrode are 4.6 cm × 5.6 cm.
7. The assembly method according to claim 1, characterized in that, In step three, the hot pressing process is as follows: under a pressure of 5 MPa, the temperature is increased from 30°C to 80°C at a rate of 10°C / min, then increased to 120°C at a rate of 5°C / min, and held at 120°C for 20 minutes.
8. The assembly method according to claim 1, characterized in that, The inert atmosphere in step four is an argon atmosphere.
9. The aramid nanofiber reinforced thermoplastic composite battery of claim 4, and its application in aerospace, electric vehicles and lightweight integrated energy storage.